2003
DOI: 10.1080/11024159850191120
|View full text |Cite
|
Sign up to set email alerts
|

The haemodynamic effect of thoracoscopic cardiac sympathectomy

Abstract: A patient with angina pectoris who had been successfully treated by thoracoscopic cardiac sympathectomy was scheduled to have scalp debridement under general anaesthesia for a scald burn. There were haemodynamic changes during and after the operation including anaesthetic induction, endotracheal intubation, maintenance, and early recovery period. The sympathetic denervated heart showed little chronotropic response to anaesthetic and surgical stimulation. On the contrary, the parasympathetic response was predom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…[11,12] The following studies also reported satisfactory results with SLT during ETSB surgery. [4,[12][13][14][15][16] Nevertheless, most of these articles report retrospective single arm studies and very few prospective studies were conducted on this matter. Two early studies comparing DLT and SLT demonstrated contradictory results in terms of intraoperative oxygenation, [17,18] adding confusion to this topic.…”
Section: Discussionmentioning
confidence: 99%
“…[11,12] The following studies also reported satisfactory results with SLT during ETSB surgery. [4,[12][13][14][15][16] Nevertheless, most of these articles report retrospective single arm studies and very few prospective studies were conducted on this matter. Two early studies comparing DLT and SLT demonstrated contradictory results in terms of intraoperative oxygenation, [17,18] adding confusion to this topic.…”
Section: Discussionmentioning
confidence: 99%
“…Since it compares with acute high dose complete beta blockade, there is a theoretical possibility of acute drop in blood preesure (BP) and heart rate (HR). These acute hemodynamic effects of bilateral CSD have been documented in few isolated case reports [ 16 ], but no substantial study has yet looked specifically for this effect in the intra-operative and immediate post-operative periods. This particular hemodynamic effect, though of smaller magnitude, has been observed in earlier studies where thoracic sympathectomy was performed for palmar hyperhidrosis and facial blushing [ [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] ].…”
Section: Introductionmentioning
confidence: 99%